Zab lam kun ʼdus Thugs rje chen poʼi smyuṅ gnas cho gaʼi don bsgrigs snaṅ byed sgron me bźugs so - O-rgyan-phrin-las-gliṅ-pa, A-paṃ Gter-ston (s.n., 1978)
Method of the ritual propitiation of Avalokiteshvara in his Eleven-faced form (Mahākāruṇika Ekādaśamukha through the observance of fasting and silence.